Maximizing rice husk waste for Daucus carotaproduction - K. P. Baiyeri; U. P. Chukwudi; C. A. Chizaram; N Aneke (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Rice husk is one of the most widely available agricultural wastes in many rice producing countries of the world. Here, we evaluated carrot production under different rice husk-amended media aimed at providing alternative use for rice husk. Methods The experimental design was 2×5×4 factorial in completely randomized design with six replications. Factor A consist of two production environments—high tunnel and open field while factor B was five growth media—5:0:0, 4:0:1, 3:1:1, 2:2:1 and 1:3:1 (topsoil:rice husk:poultry manure). Factor C was four carrot varieties; ‘Touchon’, ‘Amazonia’, ‘Carrot New Kuroda’ and ‘Touchon Mega’. Data were collected on seedling emergence and yield parameters. The analyzed means were separated using FLSD (0.05). Results The biomass yield from plants grown in high tunnel was significantly higher than plants in the open field. Highest root weight, wet and dry biomass yield were obtained from medium 4:0:1 followed by 3:1:1. Harvest index ranged from 32.3% in medium 1:3:1 to 62% in 3:1:1. Days to seedling emergence among varieties ranged from 8.5 to 11.3. ‘Amazonia’ variety produced the highest root weight, wet and dry biomass yield and was followed by ‘Touchon Mega’. Conclusion Carrot seedling emergence and yield differed in rice husk-amended media under high tunnel and open field environments. ‘Amazonia’ variety grown in media 4:0:1 or 3:1:1 gave the best yield. Inclusion of rice husk in media formulation beyond an optimum rate resulted in yield reduction in carrot. Carrot is sensitive to the physio-chemical properties of its growth medium.